Tinjauan hukum terhadap pembentukan kementerian penerimaan negara dalam rangka meningkatkan efektivitas kebijakan fiskal di indonesia: urgensi,tantangan dan implikasi - Isnaini, Rohmatika Fitri (Maliki Interdisciplinary Journal, 2026)
The establishment of a Ministry of State Revenue is considered one of the strategic steps in reforming Indonesia’s fiscal policy framework to improve state revenue management. This study aims to analyze the urgency, challenges, and implications of forming such a ministry from a legal perspective. The research method used is normative juridical, employing statutory and conceptual approaches to examine the legal basis, institutional arrangements, and international best practices related to the consolidation of state revenue authorities. The findings indicate that the formation of a Ministry of State Revenue has strong urgency to unify the functions of revenue collection, reduce inefficiency, and strengthen fiscal sustainability. However, there are several legal and institutional challenges, including regulatory harmonization, potential overlaps of authority, and the need for careful transitional arrangements. The study concludes that with adequate legal foundation and institutional design, the Ministry of State Revenue can serve as an instrument to enhance fiscal policy effectiveness in achieving national development goals.